Cerebral Palsy: Orthopedic Aspects and Rehabilitation - (:unkn) unknown (W B SAUNDERS CO-ELSEVIER INC, 2008)
Cerebral palsy is the most common chronic disability of childhood today. The concept of management rather than cure forms the basis of intervention. Therapy programs should be integrated with summer camps, home activities, and school, enabling the child and the family to live as close to normal as possible. Successful rehabilitation should prevent additional problems, minimize disability, and create a happy child.
Keywords: Cerebral palsy; Rehabilitation; Orthopedics; SELECTIVE DORSAL RHIZOTOMY; GROSS MOTOR FUNCTION; SPASTIC DIPLEGIA; RISK-FACTORS; AMBULATORY CHILDREN; MANAGEMENT; HEMIPLEGIA; BORN